Inovasi Pembelajaran Anak Usia Sekolah Dasar Melalui Video Pembelajaran - Putri Rahamadani; Dinda Amalia (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
In today’s digital era, the use of video media in learning has become one of the significant innovations, especially for elementary school children. This article discusses how video media can enhance the teaching and learning process in an engaging and interactive way. By utilizing educational, tutorial and interactive videos, students can more easily understand the concepts being taught. In addition, video media is also able to increase student engagement so that they are more active in its implementation, such as limited access to thechnology and teacher readiness. Therefore, this article also offers solutions to overcome these barriers, including training for educators and improving thechnology infrastructure in schools. Through this approach, it is hoped that learning in schools. Through this approach, it is hoped that learning in primary schools can become more effective and enjoyable for students.